2017
DOI: 10.1016/j.jtbi.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of delayed dispersal and subsequent emergence of helping, with implications for cooperative breeding

Abstract: Cooperative breeding occurs when individuals help raise the offspring of others. It is widely accepted that help displayed by cooperative breeders emerged only after individuals' tendency to delay dispersal had become established. We use this idea as a basis for two inclusivefitness models: one for the evolution of delayed dispersal, and a second for the subsequent emergence of helpful behaviour exhibited by non-breeding individuals. We focus on a territorial species in a saturated environment, and allow terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…The likelihood of filling an empty breeding position is implemented as a lottery weighted by the age of the candidates, with older individuals having a higher probability, regardless of relatedness levels. This contrasts with previous models assuming that dispersers join the queue for inheritance at the end ( 13 , 77 , 78 ) and conforms with empirical observations ( 79 , 80 ). Age was chosen as a proxy for RHP since it enables individuals to assess their competitiveness, a simplification allowing for the evolution of a simple rule to adjust helping and dispersal strategies to the likelihood of becoming a breeder.…”
Section: Methodssupporting
confidence: 81%
“…The likelihood of filling an empty breeding position is implemented as a lottery weighted by the age of the candidates, with older individuals having a higher probability, regardless of relatedness levels. This contrasts with previous models assuming that dispersers join the queue for inheritance at the end ( 13 , 77 , 78 ) and conforms with empirical observations ( 79 , 80 ). Age was chosen as a proxy for RHP since it enables individuals to assess their competitiveness, a simplification allowing for the evolution of a simple rule to adjust helping and dispersal strategies to the likelihood of becoming a breeder.…”
Section: Methodssupporting
confidence: 81%
“…Yet, correlations do not reveal causality, and in fact, a mathematical model has shown that increased survivorship, i.e. low extrinsic mortality, and/or a high fecundity, a priori select for the evolution of helping and sociality ( [53], see also [54] and, for the evolution of delayed dispersal, [55]). Thus, reinforcing feedback processes may lead to increasing lifespan and fecundity with increasing sociality, which again results in larger colony size (figure 1).…”
Section: Discussion (A) Remoulding Longevity and Fecundity In Social Animals: Causes And Consequencesmentioning
confidence: 99%
“…From an evolutionary perspective, changes in animal dispersal have been addressed in the context of delayed dispersal in the evolution of cooperative breeding (Wild and Korb 2017), evolution of density-dependent dispersal with range expansion (Fronhofer et al 2017), the single gene pleiotropic effect on local dispersal (Edelsparre et al 2014), morphological changes and specialization for limited resources (e.g. Darwin’s Finches) (Grant and Grant 2006) and the quantitative genetic variation underlying local dispersal and the rate of exploration of novel environments (Korsten et al 2013).…”
Section: Rapid Changes In Dispersal In Different Systemsmentioning
confidence: 99%